Demoliton of the Jordan Marsh Company Building at 450-472 Washington Street, 1975 - Neiley, Robert (Tufts Archival Research Center, 2005)
Street-level view east-northeast of the demolition of the Jordan Marsh Company Building, located at 450-472 Washington Street at Summer Street. Scaffolding and a covered pedestrian walkway adorn the facade of the building, which faces north-northwest. Automobiles fill Washington Street. 7 1/2 x 9 1/2 , 8 x 10 overall Photographs